In vivo Characterization of a Selective, Orally Available, and Brain Penetrant Small Molecule GPR139 Agonist - Shoblock, James R.; Welty, Natalie; Fraser, Ian; Wyatt, Ryan; Lord, Brian; Lovenberg, Timothy; Liu, Changlu; Bonaventure, Pascal (Frontiers in Pharmacology, 2019)
Recently, our group along with another demonstrated that GPR139 can be activated by L-Phenylalanine and L-Tryptophan at physiologically relevant concentrations. GPR139 is discretely expressed in brain, with highest expression in medial habenula. Not only are the endogenous ligands catecholamine/serotonin precursors, but GPR139 expressing areas can directly/indirectly regulate the activity of catecholamine/serotonin neurons. Thus, GPR139 appears expressed in an interconnected circuit involved in mood, motivation, and anxiety. The aim of this study was to characterize a selective and brain penetrant GPR139 agonist (JNJ-63533054) in relevant in vivo models. JNJ-63533054 was tested for its effect on c-fos activation in the habenula and dorsal striatum. In vivo microdialysis experiments were performed in freely moving rats to measure basal levels of serotonin or dopamine in prefrontal cortex and nucleus accumbens. Finally, the compound was profiled in behavioral models of anxiety, despair and anhedonia. The agonist (10-30 mg/kg, p.o.) did not alter c-fos expression in medial habenula or dorsal striatum nor neurotransmitter levels in prefrontal cortex or nucleus accumbens. JNJ-63533054 (10 mg/kg p.o.) produced an anhedonic-like effect on urine sniffing, but had no significant effect in tail suspension, with no interaction with imipramine, no effect on naloxone place aversion, and no effect on learned helplessness. In the marble burying test, the agonist (10 mg/kg p.o.) produced a small anxiolytic-like effect, with no interaction with fluoxetine, and no effect in elevated plus maze. Despite GPR139 high expression in medial habenula, an area with connections to limbic and catecholaminergic/serotoninergic areas, the GPR139 agonist had no effect on c-fos in medial habenula. It did not alter catecholamine/serotonin levels and had a mostly silent signal in in vivo models commonly associated with these pathways. The physiological function of GPR139 remains elusive.